El habeas data como principio al acceso a la información de una tercera persona cuando se demuestra legítimo interés. - Barrigas Cabrera, Stalin Vinicio (2011)
The present entitled thesis work, THE HABEAS DATES LIKE PRINCIPLE TO THE ACCESS TO THE INFORMATION OF A THIRD PERSON WHEN LEGITIMATE INTEREST is DEMONSTRATED whose right implies the possibility of being informed about the registered data and the ability of correcting them so much in public or private entities, to effect of protecting the intimacy of people before the growing use of personal information on the part of the Public Administration mainly, of financial, educational entities, professionals or other organizations of private character. This importance resides in that people don't lose the control about the own information as well as its use, of being manipulated this violent the access of the information of a particular person in which one has a legitimate interest of knowing the information that has character of reserved or personal, because it can be affecting to its honor and good name that to the equal it is a constitutional right to which all Ecuadorian citizen has to make it respect as own right. This right maintains a double line of safeguarding the information of the matters; on one hand it incorporates exigible obligations to public or private entities that gather and they treat information, such as of being continued by principles of loyalty, genuineness with relationship to the purpose for what the data will be gathered and on the other hand it consists on the right that has all person of demanding to the State the respect to their rights as that of the personal and family intimacy and to their good name, but this study goes directed to that in case this information this affecting a third person, this he/she has the possibility to consent it by means of a petition and the due justification that this information that has the character of reserved or protected is affecting him in its life or in turn he/she believes him an eminent damage, but provided this justification has a good one I base so much juridical and social.